Menguji Kenegarawanan Hakim Konstitusi Melalui Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 - Gusman, Delfina (Nagari Law Review, 2023)
Constitutional Justice Saldi Isra's confusion in expressing a different opinion (dissenting opinion) regarding the ruling of the Constitutional Court Number 90/PUU-XXI/2023, opening up public space to question the material aspects of the decision. According to Saldi Isra, the substance of the petition in Case Number 90/PUU-XXI/2023 is simple and clearly visible.opened legal policyIn fact, it was taken over and used as a "political burden" for the Court to decide. The results of the research explain that first, the mechanism for filling the position of Constitutional Judge greatly determines the statesmanship qualifications of Constitutional Judges, the involvement of state institutions as institutions proposing Constitutional Judges. Second, to create Constitutional Judges who master the constitution and state administration and have integrity and personality that is beyond reproach and are fair, it is necessary to make changes to the mechanism for filling the positions of Constitutional Judges in order to create a mechanism that reflects the independence of their election.